Coupling to two target-state bands in the study of the n+22 Ne system at low energy - Fraser, Paul; Canton, L.; Amos, K.; Karataglidis, S.; Svenne, J.; van der Knijff, D. (The American Physical Society, 2014)
One theoretical method for studying nuclear scattering and resonances is via the multichannel algebraicscattering (MCAS) formalism. Studies to date with this method have used a simple collective-rotor prescriptionto model target states with which a nucleon couples. While generally these target states all belong to the samerotational band, for certain systems it is necessary to include coupling to states outside of that main band. Here,we extend MCAS to allow coupling of different strengths between such states and the rotor band. This is anessential consideration in studying the example examined herein, the scattering of neutrons from 22Ne.